Towards Dynamic Policy Instruments for Enhancing Biodiversity Conservation in National Parks: A Case Study on Bangladesh and Sarawak, Malaysia - Miah, Md Rahimullah; Sayok, Alexander; Sarok, Ahi; Uddin, Mohammad Belal (Borneo Journal of Resource Science and Technology, 2017)
Asia is the most populous region, with a substantial number of global biodiversity hotspots and several megadiverse countries, including Malaysia, with rich cultural and natural heritages. In this region, natural heritages within protected areas is under threat with high tendency of biodiversity losses. Exploitation is widespread but effective conservation is hampered by lack of systematically dynamic policies and instruments. This study attempts to relook at key factors that strengthen policies towards conserving biodiversity at national parks (NPs) in Bangladesh and Sarawak, Malaysia. It focuses on the analysis and review of the present tools (policy, growth of national parks and legal aspects) used to enhance conservation activities within and around these areas through literature review, observations of some of the parks, as well as interviews with relevant staff and indigenous community. The study showed that the growth of NPs maximized for the period of 2010 to 2014 both in Bangladesh and Sarawak, Malaysia reflecting the importance that both countries are placing on the conservation of biodiversity and the ecosystem services they provide. This is indeed a positive sign that both two countries reveal towards achieving Aichi Biodiversity Target 11 for the global protected areas network. Overall, the study suggests that the dynamic policy-based decision-making on sustainable biodiversity protection at NPs in both countries should incorporate development with environmental, economic, social, institutional and administrative domains.